The Effectiveness of Hospital Management Information System Implementation in Improving Administrative Efficiency of Inpatient Services (PT. LARPA JAYA PUBLISHER, 2023)
This study aims to analyze the effectiveness of implementing the Hospital Management Information System in improving administrative efficiency in inpatient services. The research employed a mixed-method approach (quantitative and qualitative) using a descriptive survey design. The sample consisted of 50 respondents, including administrative staff, medical personnel, and hospital management directly involved in the use of Management Information System, as well as 10 key informants for in-depth interviews. Data were collected through questionnaires and semi-structured interviews, then analyzed using descriptive statistics, correlation tests, and thematic analysis. The results indicate that Management Information System has a significant positive impact on administrative efficiency, as evidenced by improvements in process speed, data accuracy, and coordination among service units. The system also contributes to accelerating claim processes and reducing the manual workload of administrative staff. However, the effectiveness of Management Information System is still influenced by factors such as human resource readiness, training, and technological infrastructure support. The main challenges identified include limited training and technical network issues. In conclusion, Management Information System has proven effective in enhancing administrative efficiency in inpatient services, but further optimization through continuous training, managerial support, and integrated system development is required for more effective implementation.